BENEFITS OF USING THE BENCHMARKING METHOD FOR INCREASING THE COMPETITIVENESS OF THE UNIVERSITY (Marketing Journal, 2025)
One of the effective ways to develop the higher education system of Uzbekistan is the introduction of innovative management methods. Benchmarking is one of the most promising technologies in this area. To implement benchmarking in university management, it is recommended to use the "20 Keys" program as a key guide. This study proposes an approach to implementing the "20 Keys" program in the use of benchmarking in higher education institutions.
Keywords: benchmarking; university management; "20 Keys" program